Sistem Informasi SMA Negeri 1 Pintu Rime Gayo Berbasis Web dan Android - Misnawati; Munar (Jurnal Tika, 2022)
The Web and Android-Based Information System for SMA Negeri 1 Pintu Rime Gayo aims to help parents find out school information so that it is hoped that it can be felt by teachers, students and other staff at SMA Negeri 1 Pintu Rime Gayo. This system was developed using the PHP and MySQL programming languages using a database that is tailored to the needs in the process of designing this information system. The things contained in this system include various information such as class data information, room data, teacher data, student data, subject data, teacher subject data, roster data, absent data, value data. The design uses a structured method that uses Context Diagrams, ERD, DFD as a tool to design an Information System for SMA Negeri 1 Pintu Rime Gayo Web-Based and Android